Chrysin, a PPAR-γ agonist improves myocardial injury in diabetic rats through inhibiting AGE-RAGE mediated oxidative stress and inflammation. (25th April 2016) - Rani, Neha; Bharti, Saurabh; Bhatia, Jagriti; Nag, T.C.; Ray, Ruma; Arya, Dharamvir Singh
Abstract: AGE-RAGE interaction mediated oxidative stress and inflammation is the key mechanism involved in the pathogenesis of cardiovascular disease in diabetes. Inhibition of AGE-RAGE axis by several PPAR-γ agonists has shown positive results in ameliorating cardio-metabolic disease conditions. Chrysin, a natural flavonoid has shown to possess PPAR-γ agonist activity along with antioxidant and anti-inflammatory effect. Therefore, the present study was designed to evaluate the effect of chrysin in isoproterenol-induced myocardial injury in diabetic rats. In male albino Wistar rats, diabetes was induced by single injection of streptozotocin (70 mg/kg, i.p.). After confirmation of the diabetes, rats were treated with vehicle (1.5 mL/kg, p.o.), chrysin (60 mg/kg, p.o.) or PPAR-γ antagonist GW9662 (1 mg/kg, i.p.) for 28 days. Simultaneously, on 27th and 28th day myocardial injury was induced by isoproterenol (85 mg/kg, s.c.). Chrysin significantly ameliorated cardiac dysfunction as reflected by improved MAP, ±LVdP/ dtmax and LVEDP in diabetic rats. This improvement was associated with increased PPAR-γ expression and reduced RAGE expression in diabetic rats. Chrysin significantly decreased inflammation through inhibiting NF-κBp65/IKK-β expression and TNF-α level. Additionally, chrysin significantly reduced apoptosis as indicated by augmented Bcl-2 expression and decreased Bax and caspase-3 expressions. Furthermore, chrysin inhibited nitro-oxidative stress by normalizing the alteration in 8-OHdG, GSH, TBARS, NO and CAT levels and Nox4, MnSOD, eNOS and NT expressions. Co-administration of GW9662 significantly blunted the chrysin mediated cardioprotective effect as there was increase in oxidative stress, inflammation and apoptosis markers. Chrysin significantly ameliorated isoproterenol-induced myocardial injury in diabetic rats via PPAR-γ activation and inhibition of AGE-RAGE mediated oxidative stress and inflammation. Highlights: Role of chrysin in myocardial infarction (MI) in diabetic rats was studied. Chrysin reduces oxidative stress, inflammation and apoptosis in diabetic hearts. This cardioprotection was attributed to PPAR-γ activation and RAGE suppression. Co-treatment with PPAR-γ antagonist, GW9662 significantly abolished this effect.